The Role of Mediation Organizational Citizenship Behavior on the Effect of Work Motivation and Job Satisfaction on Employee Performance - Jufrizen Jufrizen; Muhammad Rizky Hutasuhut (AIBPM Publisher, 2022)
The purpose of this study was to determine and analyze the effect of work motivation and job satisfaction on employee performance. To find out and analyze organizational citizenship behavior that mediates the effect of work motivation on employee performance and job satisfaction on employee performance. The research method used in this study is a quantitative method. The population in this study was the entire administrative workforce of Dr Pringadi Hospital, Medan City, amounting to 107 people. The number of samples used in this study using the Slovin formula with a total sample of 52 employees. The data used in this study is primary data by distributing questionnaires. The data analysis technique used in this research is quantitative data analysis technique using statistical methods. The statistical method used is Partial Least Square (PLS). The results showed that work motivation had a positive and significant effect on employee performance, job satisfaction had a positive and significant effect on employee performance, work motivation had a positive and significant effect on organizational citizenship behavior. Keywords: Work Motivation, Job Satisfaction, Employee Performance, Organization Citizenship Behavior